O design de artefatos tecnológicos como mediador na gestão do tempo : um estudo dos concerns conflitantes entre o pai e seus filhos - Vidaletti, Daniel Mello (Universidade do Vale do Rio dos Sinos, 2019)
This work aims to develop design guidelines for the construction of technological artifacts that can promote a better management of time in what involves the relationship of the father with his children. With the presence of the increasingly intensified father next to the division of family roles urged studies to address this relationship. Therefore, this research chose to use design for emotion, focusing on the internal conflicts (conflicting concerns) of the father. In order to do this, it was sought to understand the conflicting concerns (beliefs, attitudes and learned patterns) in the relationship between the father and his children. The research was carried out through a qualitative research, through in-depth interviews, which occurred after a period of seven-day sensitization tasks about the theme that explores the concerns between father and children. In these seven days the parents described if they experienced conflicts in the management of the time with the children and how was its possible resolution, from there, the interviews followed in depth. The interviews were recorded and after the transcription analyzed through the technique of Content Analysis. Six categories of conflicting concerns of the father were identified. The construction of guidelines for the design area occurred through the discussion with a group of designers, giving rise to four groups of guidelines in a total of 21 design guidelines in order to foster the development of technological artifacts that could serve as mediators in the relationship between fathers and children. Since technology is increasingly present in the connection between family members, whether by remote connection through the cellphone or through the internet, understanding the conflicting concerns in managing the father's time with their children can assist in the construction of technological artifacts that provide a space for healthy development for the family, helping to manage the time of the father and children relationship.
Keywords: Design para emoção; Concerns conflitantes; Gestão do tempo; Pai; Filhos; Design for emotion; Conflicting concerns; Time management; Father; Children; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial